Las primeras reglas jurídicas de Estados Unidos (2006)
From a non professional historical perspective, this article seeks to analyze the sociopolitical frame that fostered the early legal discourses in the American continent. It is an initial assumption the comparison between discovery and colonization processes of North American and South American territories. Given the outcomes of the first explorations, it is stated that the foreign affairs policy of England and Spain take different routes and, consequently, the respective legal discourses are built. At the end, decisions on establishing a looting economy or a market economy were deeply influenced by the discovery contingency.